2020
DOI: 10.3390/land10010016
|View full text |Cite
|
Sign up to set email alerts
|

Landscape-Based Visions as Powerful Boundary Objects in Spatial Planning: Lessons from Three Dutch Projects

Abstract: In a context of a rapidly changing livability of towns and countryside, climate change and biodiversity decrease, this paper introduces a landscape-based planning approach to regional spatial policy challenges allowing a regime shift towards a future land system resilient to external pressures. The concept of nature-based solutions and transition theory are combined in this approach, in which co-created normative future visions serve as boundary concepts. Rather than as an object in itself, the landscape is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Conclusions have shown that this case-study was an "extreme/deviant case" (Flyvbjerg 2006), and it cannot be generalized due to its specific political context. Despite this, in the literature, it can be find other authors and case-studies (van Rooij et al 2021) that also argue that the landscape approaches and the landscape scale must be mainstreaming on spatial planning and coastal planning literature and practice.…”
Section: The Conventional Planning Practice and Its Interrogationmentioning
confidence: 99%
“…Conclusions have shown that this case-study was an "extreme/deviant case" (Flyvbjerg 2006), and it cannot be generalized due to its specific political context. Despite this, in the literature, it can be find other authors and case-studies (van Rooij et al 2021) that also argue that the landscape approaches and the landscape scale must be mainstreaming on spatial planning and coastal planning literature and practice.…”
Section: The Conventional Planning Practice and Its Interrogationmentioning
confidence: 99%
“…In addition, when drip irrigation is installed on formerly terraced landscapes, the bunds or terrace structures are generally removed to rationalize farming operations, which leads to severe erosion events owing to the long slope lengths created. Thus, it is important to keep the sustainability of the landscape in mind during the planning of land-use and agricultural investments [60,61]. Nature-based solutions are needed to avoid land degradation and to help achieve sustainability in the use of natural resources and the livelihoods of farmers [24,25].…”
Section: (Ii) Downstream Water and Erosion Problems Related To Poor Water Managementmentioning
confidence: 99%
“…The process helped participants discuss how not everything is possible, but a lot might be, especially when underpinned by a joint sense of what the overall direction should be. Collaboratively created visions serve as a boundary objective to have constructive conversations about what that direction should be (van Rooij et al 2021). Such visions can, and even should, be pluralistic (McPhearson et al 2016); they do not have to be fully shared among actors to provide a target space for collaboration.…”
Section: Reflections On the Approachmentioning
confidence: 99%